Letter - Paterson, J.
028-0195-001 UNION OF POST-OFFICE WORKERS TELEGRAPHIC ADDRESS: "POSTACT, SOUTHKENS" TELEPHONE NO.: KENsington 0155 43, CROMWELL ROAD, SOUTH KENSINGTON, LONDON, S.W.7. MEMO FROM: T. J. HODGSON, General Secretary. Ref No. G.IN/8/36 Your Ref. T J.T. Enclosures 8th September, 1936. Mr. H. V. Tewson, Assistant General Secretary, Trades Union Congress Office, Plymouth. Dear Mr. Tewson, As you will probably know, this Union has made an appeal to all branches on behalf of the Relief Fund for Spanish Workers. This has led to certain criticisms, particularly from Catholic members of the Union, who object to the Workers' Party in Spain on religious grounds. I am not particularly concerned about this aspect of the case, but we have received enquiries as to how the Fund will be used, and what guarantees can be given that any monies collected will get to the right people. I was in telephone communication with your department in London yesterday morning, and as the matter was rather urgent, they suggested that I should write to you direct. I shall be glad if you will let me have an early reply. Yours sincerely, J. Paterson, Assistant General Secretary. 292/946/28/195